2018
DOI: 10.1016/j.envint.2017.10.024
|View full text |Cite|
|
Sign up to set email alerts
|

Acute effects of ambient air pollution on lower respiratory infections in Hanoi children: An eight-year time series study

Abstract: Strong associations between hospital admissions for lower respiratory infections and daily levels of air pollution confirm the need to adopt sustainable clean air policies in Vietnam to protect children's health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
107
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 32 publications
9
107
1
8
Order By: Relevance
“…PM 2.5 , PM 1 are health-damaging particles not only because of their chemical components but because they can penetrate deep inside the lungs to aggravate existing asthma or to contribute to the development of chronic bronchitis (20,(49)(50)(51). Our meta-analyses showed wheeze-associated disorders were most strongly associated with PM 1 , which was consistent with the limited literature available on fine particles (46,52,53). Earlier evidence indicated that the small particles can reach bronchioles and penetrate up to the primary, secondary terminal bronchi, and alveoli in the lung which may trigger mucous secretions in airways, reduce air flow and then cause wheezing (54,55).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…PM 2.5 , PM 1 are health-damaging particles not only because of their chemical components but because they can penetrate deep inside the lungs to aggravate existing asthma or to contribute to the development of chronic bronchitis (20,(49)(50)(51). Our meta-analyses showed wheeze-associated disorders were most strongly associated with PM 1 , which was consistent with the limited literature available on fine particles (46,52,53). Earlier evidence indicated that the small particles can reach bronchioles and penetrate up to the primary, secondary terminal bronchi, and alveoli in the lung which may trigger mucous secretions in airways, reduce air flow and then cause wheezing (54,55).…”
Section: Discussionsupporting
confidence: 87%
“…Based on the data in Table 1, nearly 84,000 pediatric wheeze-associated disorders events have been investigated to assess the impact of ambient air pollution in five countries. Of these, four studies were conducted in Thailand (7,(41)(42)(43), three in Vietnam (44)(45)(46), and one each in Singapore, Indonesia and Malaysia (8,9,47).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations